USING TURKISH SOAP OPERAS (TV SERIES) AS A MARKETING COMMUNICATION TOOL: A RESEARCH ON TURKISH SOAP OPERAS IN KAZAKHSTAN - Niyazi GÜMÜŞ; Gülzira ZHAXYGLOVA; Maiya MİRZABEKOVA (International Journal of Eurasia Social Sciences, 2017)
In order to survive in the highly-competitive environment and to reach as many consumers as possible, brands make changes in the marketing communication tools they employ. Presently television soap operas (TV series) are decidedly one of the most effective marketing communication channels frequently utilized by brands. Via placing their products in soap operas or endorsing the television characters with their brand or products, modern brands seek to impress the consumers. Within that context, Turkish soap operas have lately gained much popularity in a good number of regional states particularly Middle Eastern, Balkans and Caucasus countries. It is thus the purpose of present study to analyze using Turkish soap operas aired as a marketing communication tool in Kazakhstan and investigate its effects. The face-to-face interview concocted within the scope of this research was conducted between 1-25 March 2016 among 186 citizens residing in Kazakhstan- Almaty city and were selected via convenience sampling method.